Endometrial osseous metaplasia: clinicopathological study of a case and literature review - T., Ramya; T.V., Chitra; C., Poornima; B., Anjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Endometrial ossification is a rare clinical condition related to menstrual disturbances and infertility. Its etiology and pathogenesis are controversial. The commonly accepted hypothesis is that ossification represents retained fetal bones following spontaneous or therapeutic abortion suggesting enchondral ossification. It can also be due to transformation of mesenchymal tissue to bone in response to chronic inflammation. We present one such case in a 41 year old woman who presented with menorrhagia and dysmenorrhoea following induced abortion 16 years back at 12 weeks of gestation. The patient underwent hysterectomy. We also present a literature review.